MICROBIAL DYNAMICS DURING VARIOUS ACTIVITIES IN RESIDENTIAL AREAS OF LAHORE, PAKISTAN - S. Sidra; Z. Ali; S. Sultan; S. Ahmed; I. Colbeck; Z. A. Nasir (Journal of Animal and Plant Sciences, 2015)
Bioaerosols are ubiquitous in the atmosphere with their levels affected by a variety of environmental factors as well as type of activities being carried out at any specific time. The present study investigated how indoor activities influence bioaerosol concentrations in five residential houses of Lahore. Agar coated petri plates were exposed face upwards for twenty minutes in kitchens and living rooms during activity and non-activity periods. The temperature and relative humidity levels were noted as well. The bioaerosol concentrations in kitchens during the activity time ranged between 3 3 1022 to 4481 cfu/m and in living rooms from 1179 to 3183 cfu/m . Lower values were observed during non-activity periods. A paired-t test revealed a significant difference in bacterial loads during activity and non-activity times in both micro-environments (p = 0.038 in kitchen and p = 0.021 in living room). The predominant species identified were Micrococcus spp., Staphylococcus spp., and Bacillus spp. which are a common constituent of the indoor environment and are known to be opportunistic pathogens as well.
Keywords: NA